2019
DOI: 10.1158/2159-8290.cd-19-0138
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics and Single-Cell Sequencing Define a Developmental Hierarchy in Langerhans Cell Histiocytosis

Abstract: Langerhans cell histiocytosis (LCH) is a rare neoplasm predominantly affecting children. It occupies a hybrid position between cancers and inflammatory diseases, which makes it an attractive model for studying cancer development. To explore the molecular mechanisms underlying the pathophysiology of LCH and its characteristic clinical heterogeneity, we investigated the transcriptomic and epigenomic diversity in primary LCH lesions. Using single-cell RNA sequencing, we identified multiple recurrent types of LCH … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 61 publications
3
67
1
1
Order By: Relevance
“…Second, we explored the utility of the GEN KPNN for analyzing disease-associated cell states in Langerhans cell histiocytosis (LCH), a rare developmental disorder that combines relevant aspects of a cancer and of an autoinflammatory disease [ 78 ]. Based on a recently published single-cell RNA-seq analysis of LCH [ 51 ], we trained the GEN KPNN to distinguish between progenitor-like and mature LCH cell populations described previously. We obtained separate KPNN models for (i) bone-derived LCH cells from patients with relatively benign single-system disease and (ii) skin-derived LCH cells from patients with aggressive multi-system disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, we explored the utility of the GEN KPNN for analyzing disease-associated cell states in Langerhans cell histiocytosis (LCH), a rare developmental disorder that combines relevant aspects of a cancer and of an autoinflammatory disease [ 78 ]. Based on a recently published single-cell RNA-seq analysis of LCH [ 51 ], we trained the GEN KPNN to distinguish between progenitor-like and mature LCH cell populations described previously. We obtained separate KPNN models for (i) bone-derived LCH cells from patients with relatively benign single-system disease and (ii) skin-derived LCH cells from patients with aggressive multi-system disease.…”
Section: Resultsmentioning
confidence: 99%
“…The LCH dataset [ 51 ] was downloaded from GEO (GSE133704). Single-cell annotations were downloaded from http://www.medical-epigenomics.org/papers/LCH_hierarchy/data/lch_10x_meta.csv.gz as of 1 October 2019.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have already demonstrated that LCH-cells express the co-stimulatory receptors CD40 (10)(11)(12), CD80 (3, [11][12][13], ICOS ligand (ICOSL) (14) and, although variably, CD86 (3, 11,12) in situ. Moreover, transcriptome analyses revealed that LCH-cells express similar levels of CD40, CD80, and CD86 messenger RNA when compared to normal epidermal CD207 + Langerhans cells (15,16), and that they confer high expression of genes relevant for antigen presentation (including CD1E) and genes encoding members of the HLA (class II) complex (17). Thus, LCH-cells do not appear to have an intrinsic defect in their capacity to elicit a T cell immune response (12).…”
Section: Introductionmentioning
confidence: 99%